Indicators for monitoring and evaluating research-for-development: A critical review of a system in use - Belcher, Brian M.; Claus, Rachel; Davel, Rachel; Place, Frank (Elsevier, 2024)
Research-for-development (R4D) refers to research activities specifically designed to address critical social, environmental, and economic challenges and improve human well-being. It is essential to have well-designed indicators to monitor and evaluate progress, guide decision-making, and support learning and improvement. This paper reviews and compares two sets of indicators in use by a large international research consortium: i) ad hoc indicators developed by and for individual (non-pooled) projects, and ii) a standard set of indicators designed as part of a common results framework for a new portfolio of research initiatives. We assess both sets of indicators against the SMART (specific, measurable, achievable, relevant and time-bound) criteria, identify common errors in indicator formulation, compare the thematic coverage of the two sets of indicators, and derive lessons for improved indicator formulation. A large proportion of the non-pooled indicators fail to meet the SMART criteria. The indicators in the standard set are stronger, but with scope for improvement, especially in terms of relationship to the result of interest, specification of the indicator, measurability, standardization of outcome indicators, and impact indicators. We recommend having a balanced set of indicators of key outputs, outcomes, and impacts, based on clear and well-defined result statements.